Development of tomato paste from a local tomato (Lycopersicum esculentum Var. "Pope") variety - Corpuz, Cynthia G.
The possibility of processing local tomato varieties into tomato paste was studied. Different tomato varieties were sampled and tested for moisture and total solids content. The sample which yielded the highest % total solids and consequently, the lowest % moisture was considered the proper raw material for this study. Using a standard procedure, tomato paste was made out of the selected tomato (Lycopersicum esculentum var. 'Pope') variety. The variables studied during the development of the products were levels of total solids (25%, 29% and 33%) of the tomato paste samples. Results of the sensory evaluation indicated that the 33% total solids level gave the most acceptable product. Analysis of data obtained from the sensory evaluation and results of the objective evaluation showed that no significant differences in color and flavor existed among the samples but texture differences, in terms of consistency, were the characteristic tomato color and flavor were maintained.